PROSPECTIVE STUDY OF THE SIDE EFFECTS BETWEEN ATYPICAL–ATYPICAL ANTIPSYCHOTIC COMBINATIONS WITH TYPICAL-ATYPICAL ANTIPSYCHOTIC COMBINATIONS ON THE PSYCHOTIC DISORDERS INPATIENTS - FUTIHAT, CHILYATI EKY; DARMAWAN, ENDANG; IKAFITRIANI, ASTRIT (International Journal of Current Pharmaceutical Research, 2020)
Objective: Antipsychotic therapy is the main therapy in psychotic disorders. Antipsychotics use often causes various side effects, such as the orthostatic hypotension, weight gain, and waist circumference. The study objective is to prove these side effects on combination therapy of atypical-atypical and typical-atypical antipsychotics on the psychotic disorders in patients. Methods: This study method is a prospective cohort applied to psychotic disorders inpatients. This study is composed of 2 different groups(n=16). Data analysis using Risk Relative Ratio for orthostatic hypotension study variables and statistical difference test with 95% confidence level for study variables of weight gain and waist circumference. Results: The p value showed that there was no significant side effects of orthostatic hypotension (p>0.05). Relative Risk Ratio (RR) value explained that the atypical-atypical antipsychotic combination group had opportunity to cause orthostatic hypotension side effects by 2,000 times greater than the typical-atypical antipsychotic combination group at 0th week observation and 1,667 times greater than the typical-atypical antipsychotic combination group at 1st and 2nd week observations. Atypical-atypical antipsychotic combinations use and typical-atypical antipsychotic combinations use cause insignificant weight gain (p>0.05). Typical-atypical antipsychotic combination use in the 2nd week increases waist circumference greater than atypical-atypical antipsychotic combination use in the 2nd week (p<0.05). Conclusion: Typical-atypical antipsychotic combinations use and atypical-atypical antipsychotic combination use did not cause significant on orthostatic hypotension and weight gain. Significant test results appear on the waist circumference increasing in the second week of typical-atypical antipsychotic combinations use when compared to atypical-atypical antipsychotic combinations use.